STUDI ANALISA PEMBENTUKAN EDUPRENEURSHIP MARITIM DI POLITEKNIK MARITIM NEGERI INDONESIA - Sri Tutie Rahayu (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2019)
The study of the Analysis on Need of Maritime Edupreneurship Program at Politeknik Maritim Negeri Indonesia (Polimarin) started from the hope that the young generation as well as the workforce in the maritime field had to have entrepreneurial spirit and from the hope to create edupreneurship at Polimarin. By considering the level of study in Polimarin, it will be difficult to built business spirit in every academic force in Polimarin, because D3 Program has only 3 years length of study. The method applied in taking research data was interviews to respondents in various forum, ie: in-depth interviews and focused group discussions. This study sought and found conditions for entrepreneurial behavior from all lines of Polimarin academics as well as the conditions of entrepreneurship learning conducted at Polimarin. Respondents in this study were students, lecturers, stakeholders, Polimarin’s alumni and Director of Polimarin. The results obtained are: Polimarin educators have the opportunity and potential to create and innovate, Polimarin’s students need practical entrepreneurship courses, entrepreneurial spirit needs to be grown in every line, both from top management, from education staff, educators and students at Polimarin’s environment and there is a need of to build maritime edupreneur program in Polimarin in systematic ways.